Excess Volume of Binary Mixtures of Water (Methanol or Ethanol) with an Ionic Liquid [EEIM][DEP] or [BEIM][DEP] at 1 atm and (293.15 to 333.15) K - Song, Hong-Yan; Gong, Yin-Hui; Jiang, Xue-Mei; Lib, Chun-Xi (Journal of Applied Solution Chemistry and Modeling, 2014)
Densities were measured for the binary mixtures of water (methanol or ethanol) and an ionic liquid (IL) 1,3-diethylimidazolium diethylphosphate [EEIM][DEP] or 1-n-butyl-3-ethylimidazolium diethylphosphate [BEIM][DEP] at 1 atm and (293.15 to 333.15) K using a vibrating-tube densimeter. The molecular volume, standard entropy, and lattice energy of the two ILs were estimated with the Glasser theory. The excess volumes are negative for all binary mixtures studied in the whole composition range, and reach to the maximum at the mole fraction of IL being around 0.3. Besides, they decrease with increasing temperature for the aqueous solution of ILs, whilst a reverse trend is found for the IL solutions of methanol or ethanol at any concentration. The excess molar volumes were correlated successfully by a five-parameter polynomial equation as a function of temperature and mole fraction of IL with average absolute relative deviation (ARD) of density within 0.02%.